2013
DOI: 10.1039/c3cp50585e
|View full text |Cite
|
Sign up to set email alerts
|

The effects of surface curvature on the adsorption of surfactants at the solid–liquid interface

Abstract: The adsorption of surfactants from dilute oil solutions on to solid surfaces is studied as a function of surface curvature and surface coverage. Coarse-grained molecular models, computer simulations, and umbrella sampling are used to compute the dependence of the free energy of adsorption on to a spherical colloid surface with radius R. It is shown that for fixed surface coverage, and with all other things being equal, the free energy of adsorption decreases with decreasing R. For fixed surface curvature, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 35 publications
0
20
1
Order By: Relevance
“…One inter-esting problem is how the adsorption of molecules depends on surface curvature, with all other parameters being held equal (specifically, bulk concentration and adsorption energy). This situation was studied using a coarse-grained model of surfactant molecules in an implicit solvent, adsorbing on to structureless spherical surfaces with a fixed radius of curvature R [56]. It was found that, for a given bulk concentration of surfactant, the adsorption decreases with increasing particle radius.…”
Section: Adsorption At the Metal-oil Interfacementioning
confidence: 99%
“…One inter-esting problem is how the adsorption of molecules depends on surface curvature, with all other parameters being held equal (specifically, bulk concentration and adsorption energy). This situation was studied using a coarse-grained model of surfactant molecules in an implicit solvent, adsorbing on to structureless spherical surfaces with a fixed radius of curvature R [56]. It was found that, for a given bulk concentration of surfactant, the adsorption decreases with increasing particle radius.…”
Section: Adsorption At the Metal-oil Interfacementioning
confidence: 99%
“…Relating to the influence of curvature, Farrow, et al [21] modelled adsorption of oil in a solution onto solid surfaces, showing an increase in surface coverage with solute is due to the geometrical effect of increased surface curvature resulting in more free volume for the solute [21]. Summarised further, the effect of curvature on sorption results in smaller particle surfaces receiving significantly greater coverage when compared to the surface of a larger particle in mutual equilibrium between the solutes and solvent [21]. Furthermore, issues with standardisation of published methods (varying results between instruments and difference in applied terminology e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we are aware there have been no other MD simulations of overbased detergents in the intervening years. Most of the mod-elling work in relation to oil additives has been on the surfactants in the oil, using either Density Functional Theory (DFT) [28] or MD [29,30]. With the improved software we are able to explore new aspects of the overbased particles under more realistic conditions.…”
Section: Introductionmentioning
confidence: 99%